Trimorphism of N-methylurea: crystal structures, phase transitions and thermodynamic stabilities. Issue 25 (24th May 2016) - Baaklini, G.; Gbabode, G.; Clevers, S.; Négrier, P.; Mondieig, D.; Coquerel, G.
Abstract : FormII and FormIII of N -methylurea were obtained after melt-quenching at −50 °C and −173 °C respectively. A reversible solid–solid transition (FormIII → FormII ) was detected at −118 °C by DSC. Abstract : Melt crystallization of N -methylurea (NMU) was investigated by X-ray and differential scanning calorimetry (DSC) techniques. In addition to the known orthorhombic stable FormI, two new polymorphic forms (II andIII ) crystallizing in the centrosymmetric space group P 21 / c were obtained at different quenching temperatures. The crystal structures of FormsII andIII were determined from X-ray powder diffraction data. The crystallographic results for the monoclinic forms are presented in this study, as well as a detailed comparison of crystal structures of the three polymorphs. The nature of hydrogen bonds in FormII and FormIII were found to be similar; hence, a first order mechanism governed by means of shear movements is suggested where a transition via nucleation and growth could occur at low temperatures. The relative thermodynamic stabilities of the three forms of NMU were investigated by DSC analyses. FormII and FormIII exhibited a reversible solid–solid phase transition at circa −118 °C. Both forms were found to be monotropically related to the stable FormI .